Parameters That Affect Fear Responses in Rodents and How to Use Them for Management - Bedoya-Pérez, Miguel A.; Smith, Kristie Leigh; Kevin, Richard C.; Luo, Jia Lin; Crowther, Mathew S.; McGregor, Iain S. (Frontiers in Ecology and Evolution, 2019)
The strong innate fear response shown by laboratory rodents to predator cues could provide powerful and innovative tools for pest management. Predator cues are routinely used to induce fear and anxiety in laboratory rodents for pharmacological studies. However, research on the fear response induced by predator cues in different species of rodents in the wild has been inconclusive and often contrary to laboratory experiments. Potential explanations for this inconsistency include the prey’s: (i) physiological state; (ii) parasite load; (iii) differential intensity of perceived threats; (iv) fear learning and habituation; and (v) information gathering. In this review, we first explore current knowledge on the sensory mechanisms and capabilities of rodents, followed by the discussion of each of these explanations within the context of their implications for the use of antipredator response as a pest rodent’s management tool. Finally, we make recommendations on potential solutions and strategies to resolve issues in rodent management related to these hypotheses.